CONVERGENT AND DIVERGENT FEATURES OF PORTUGUESE AND SPANISH RIDDLES AND SPECIFICITY OF THEIR TRANSLATION INTO UKRAINIAN LANGUAGE - Orlychenko, Olena (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2024)
To be considered folklore, a phenomenon must have certain characteristics, namely: to have an anonymous origin, to be ancient and popular, to be used and shared by many people in a certain region, to be spread orally.A riddle is a very ancient literary form, which mainly consists of a question and an answer (key). Another common type of riddles acquires a more descriptive-narrative character and in its popular versions is often presented in rhyming poems.Riddles are directly related to the play of words and ambiguous semantic associations. In ancient times, solving riddles was considered the effort of scientists and sages. Nowadays, it is an entertainment for people of any age.There are many types of riddles, each of which has its own model of creation and method of decoding. The structure of riddles is simple, in the vast majority they consist of only two sentences (question and answer), and they give the most obvious characteristics of the object that needs to be guessed.These language units can have both interrogative and less often affirmative forms, can be rhyming or not, confusing and tricky or extremely simple, although this is not a complete list of possible variants of riddles structure in Portuguese, Spanish and Ukrainian languages, which served as empirical material for this study. In general, the convergence of basic forms is observed in Portuguese, Spanish, and Ukrainian riddles, but at the same time there are differences (divergent features). Riddles are often constructed in such a way as to create the impression of a paradox, confusing everyone who hears or reads them.The problem to translate Portuguese and Spanish riddles into Ukrainian is multifaceted and consists, first of all, in reproducing the play of words, as the leveling of the latter affects not only the purpose of the original, but also completely blurs the meaning of the riddle.___________References:• https://uk.wikipedia.org/wiki• https://uk.wikipedia.org• Fandango shcho take fandango znachennia i tlumachennia slova, vyznachennia termina. https://jak.koshachek.com/articles/fandango-shho-take-fandango-znachennja-i.html#-google_vignette• Adivinanza. https://es.wikipedia.org/wiki/Adivinanza• Carvalho Sousa, Filomena. Cultura e expressões orais: A adivinha. https://fileview.-fwdcdn.com/?url=https://mail.ukr.net/api/public/file_view/list%3Ftoken%3D5GM8rBa TdgCRTMzMXjMsswl8rZjGw-0wST_FU3FFWOYI_GSCAFwm_KeNeqPfDMMv GzgHQVlB-GABMk2Wv7Aq43pvHFUyXzHY:fAXjuS-DmevXzCnG%26r%3 D1698919590554-&default_mode=view&lang=ru#start=0• Morote Magán, Pascuala. Juegos de lengua y literatura. adivinanzas y trabalenguas. Universitat de Valencia, España. https://cvc.cervantes.es/ensenanza/biblioteca_-ele/aepe/pdf/congreso_45/congreso_45_18.pdf• Peña Hernández, Enrique. (1968). Folklore de Nicaragua. Masaya, Nicaragua, Centroaméruca.• Reusner, Nicolaus. Aenigmatographia Sive sylloge aenigmatum et griphorum convivalium: ex varijs & diversis auctoribus, tam antiquis, quam novis, collectorum, & uno volumine comprehensorum Draudius & Angelus, 1599. https://books.google.com.ua/-books/about/Aenigmatographia_Sive_sylloge_ aenigmatum.html?id=aeTEngEACAAJ&redir_esc=y• Rosário Rosa Da(s) adivinha(s): da expressão oral ao jogo simbólico. https://www.researchgate.net/publication/347662826_Das_adivinhas_da_expressao_oral_ao_jogo_simbolico• Salvador Latin Riddles [Enigmata]. The Literary Encyclopedia. http://www.litencyc.com/php/stopics. php?rec=true&UlD= 1596 (дата звернення: 14.12.2012).• 30 zahadok ukrainskoiu movoiu (z vidhadkamy). http://doshkolenok.kiev.ua/zagadki/224-zagadki-ykraunskoj-movoj.html• 100 zahadok ukrainskoiu movoiu z vidpovidiamy. https://spadok.org.ua/mova-i-pysemnist/100-zagadok-ukrayinskoiu-movoiu-z-vidpovidyamy#google_vignette• Zahadka pro chasnyk na ukrainskii movi. http://korusno-znatu.in.ua/inshe/zagadky/zagadka-pro-chasnyk/#google_vignette• Zahadky Leonida Hlibova. https://mala.storinka.org/%D0%B7%D0%B0%D0%B3%D0% B0%D0%B4%D0%BA%D0%B8-%D0%BB%D0%B5%D0%BE%D0%BD%D1% 96%D0%B4%D0%B0-%D0%B3%D0%BB%D1%96%D0%B1%D0%BE%D0% B2%D0%B0.html• Zahadky na bibliinu tematyku. https://www.scribd.com/document/490362511/ %D0%97%D0%90%D0%93%D0%90%D0%94%D0%9A%D0%98-%D0%9D%D0 %90-%D0%91%D0%86%D0%91%D0%9B%D0%86%D0%99%D0%9D%D0%A3-%D0%A2%D0%95%D0%9C%D0%90%D0%A2%D0%98%D0%9A%D0%A3-docx• Zahadky pro imia. https://vseosvita.ua/library/embed/0018ii-b35c.doc.html• Zahadky pro izhu na ukrainskii movi. https://dovidka.biz.ua/zagadki-pro-yizhu-na-ukrayinskiy-movi• Zahadky pro konia, kobylu, losha ukrainskoiu movoiu. https://mega-znaika.com.ua/zahadky-pro-konya-kobylu-losha-ukrajinskoyu-movoyu/#google_vignette• Zahadky pro telefon ukrainskoiu. https://dovidka.biz.ua/zagadki-pro-telefon-ukrayinskoyu• Zahadky ukrainskoiu movoiu. http://doshkolenok.kiev.ua/zagadki/224-zagadki-ykraunskoj-movoj.html#google_vignette• Zahadky ukrainskoiu movoiu. https://kolobook.org/zagadki-ukrainskoyu-movoyu• https://uk.wikipedia.org/wiki/%D0%9C%D0%BE%D0%BD%D0%B4%D0% BE%D0%BD%D0%B3%D0%BE• https://pustunchik.ua/ua/checkyourself/zagadki/zagadki-ob-ekzoticheskikh-ptitsakh#google_vignette• Ukrainski zahadky. http://zagadki1.ru/ua/zagadky-pro/zagadky-pro-vinyk.htm#google_ vignette• Ukrainski zahadky. https://zagadki.in.ua• Ukrainski zahadky: krashchi z krashchykh. https://vsviti.com.ua/society/57805• https://ru.wikipedia.org/wiki/%D0%A4%D0%B0%D0%BD%D0%B4%D0% B0%D0%BD%D0%B3%D0%BE• 61 adivinhas infantis para divertir a criançada. https://www.todamateria.com.br/adivinhas• 101 Adivinanzas chilenas para niños y niñas (Spanish Edition) Tapa blanda – 16 Noviembre 2021. https://www.amazon.com/-/es/Enrique-Marchant/dp/ 9563249097• Acertijos y adivinanzas populares. https://www.pocoyo.com/adivinanzas/ populares• Adivinanzas y Acertijos Populares. https://www.mexgrocer.com/ adivinanzas.html• Adivinanzas, cortas y de origen mexicano. https://www.mexicodesconocido.com.mx/adivinanzas-cortas-y-de-origen-mexicano.html• https://www.todamateria.com.br/adivinhas/#google_vignette• Adivinhas com Respostas. https://educamais.com/adivinhas-com-respostas/#google_ vignette• Adivinhas infantis para brincar, entreter e aprender. https://www.brincacomigo.pt/ adivinhas-infantis-para-brincar-entreter-e-aprender/• pt. https://adivinhas.pt/• Adivinhas: qual é coisa qual é ela…? 10 adivinhas portuguesas, 18 com animais e 15 que são hilariantes! Já conhecem todas? https://pumpkin.pt/familia/atividades-com-miudos/brincar-brinquedos-criancas/adivinhas/• Atividades que estimulam a memória #8 Adivinhas. https://apexa.org/ atividades-que-estimulam-a-memoria-8-adivinhas/• Adivinhas infantis para brincar, entreter e aprender. https://www..pt/adivinhas-infantis-para-brincar-entreter-e-aprender/• Enigmas, charadas ou adivinhas: A arte de complicar algo simples. https://critico6.blogspot.com/2016/09/enigmas-charadas-ou-advinhas-arte-de.html• Feijóo, Samuel. (1981). Del piropo al dicharacho (Folklore oral de Cuba). La Habana: Letras cubanas.• Filomena Carvalho Sousa. Cultura e expressões orais: A adivinha. https://fileview.fwdcdn.com/?url=https://mail.ukr.net/api/public/file_view/list%3Ftoken%3D5GM8rBaTdgCRTMzMXjMsswl8rZjGw-0wST_FU3FFWOYI_GSCAFwm_ KeNeq-PfDMMvGzgHQVlBGABMk2Wv7Aq43pvHFUyXzHY:fAXjuS-DmevXzCnG%26r%3D-1698919590554&default_mode=view&lang=ru#start=0• https://es.educaplay.com/recursos-educativos/2618075-la_escoba.html• Peña Hernández, Enrique. (1968). Folklore de Nicaragua. Masaya, Nicaragua, Centroaméruca.• Portal São Fransico. Adivinhas• Qual é coisa, qual é ela? 50 adivinhas com respostas para crianças. https://pumpkin.pt/familia/atividades-com-miudos/brincar-brinquedos-criancas/adivinhas/• https://www.todamateria.com.br/adivinhas
Keywords: small forms of folklore, riddle-question, riddle-narrative, riddle-verses, initial and final formulas, play of words translation, free translation